A Comparative study of the translations of Clarice Lispector’s repeated fragments: a corpus-based investigation - de Souza Lima, Thereza Cristina (2013)
Our research is mainly based on Corpus-based Translation Studies (Baker 1993, 1995, 1996, 2000, 2004; Blum-Kulka, 1986; Camargo 2005, 2007; and Scott 1998) and is related to one type of cross-cultural communication, the Brazilian literature translated into the English language. It is also based on the literary studies of (Gotlib 1993; Nunes, B. 1995; Ruggero 2000; Sá, O. 2000; Varin 2002; and Cherem 2003). The current study has two main objectives: the first one aims at investigating aspects of normalization in the translation of three books, written by Clarice Lispector – A Descoberta do Mundo (DM), translated by Giovanni Pontiero as Discovering the World (DW); Uma Aprendizagem ou O Livro dos Prazeres (ALP) translated by Richard A. Mazzara and Lorri A. Parris as An Apprenticeship or The Book of Delights (ALP); and Água Viva (AV), translated by Elizabeth Lowe and Earl Fitz as The Stream of Life (TSL). As one of the main characteristics of the author is repetition, we have selected two fragments, which have been repeated in the three books analysed and translated by the different translators mentioned. This has enabled us to reach our second objective, which is to observe and compare these translators, whose source texts are the similar fragments, in relation to their own stylistic patterns.